FOOD INTAKE, FOOD PURCHASING ACCESS, AND STRESS DURING THE COVID-19 PANDEMIC: A DESCRIPTIVE STUDY AMONG COLLEGE STUDENTS OF JENDERAL SOEDIRMAN UNIVERSITY - Izka Sofiyya Wahyurin; Ajeng Dian Purnamasari; Hiya Alfi Rahmah (Media Gizi Indonesia, 2022)
The COVID-19 pandemic is causing social restrictions that leads to school form home. Long period of online learning system will likely make excessive food intakes and adolescent would try popular diet, got high stress due to staying at home for a long period of time, and decreased of food purchasing access. This study aimed to describe the food intakes, food purchasing access, and stress level among college students of Jenderal Soedirman University during pandemic period. This study was crossectional design study with data collection using purposive sampling. Total samples were 361 students from Jenderal Soedirman University Students. Descriptive Analytical data was shown using percentage, mean, and standard deviation. Food intake data was collected using 24 hours food recall and food purchasing access was determined by the online questionnaire with question about how the respondents get the access to buy food during pandemic Energy intakes, macro nutrients, vitamins C and vitamins A of Jenderal Soedirman University Students during pandemic era were inadequate compared to their nutritional needs. Most of the students feel stressed during pandemic because they were worried they might get infected by COVID-19 either themselves or their family.